Implementation Of AI In Event Marketing Strategy: Literature Review And Implications For The Event Industry In Bali - I Wayan Adi Pratama; Dewa Putu Oka Prasiasa (Politeknik Internasional Bali, 2025)
This literature review explores the implementation of Artificial Intelligence (AI) in event marketing strategies and its implications for the event industry in Bali. The study aims to understand how AI can enhance operational efficiency and attendee experience by analyzing its applications in personalization, data analysis, and predictive analytics. Despite the benefits of AI, such as improved attendee engagement and operational efficiency, challenges like data privacy and digital infrastructure limitations in Bali must be addressed. The research provides insights for event organizers and policymakers to leverage AI effectively, contributing to Bali's position as a premier event destination.